Lifestyle modification in older versus younger patients with coronary artery disease - Jepma, Patricia (Heart, 2020)
OBJECTIVE: To compare the treatment effect on lifestyle-related risk factors (LRFs) in older (≥65 years) versus younger (<65 years) patients with coronary artery disease (CAD) in The Randomised Evaluation of Secondary Prevention by Outpatient Nurse SpEcialists 2 (RESPONSE-2) trial. METHODS: The RESPONSE-2 trial was a community-based lifestyle intervention trial (n=824) comparing nurse-coordinated referral with a comprehensive set of three lifestyle interventions (physical activity, weight reduction and/or smoking cessation) to usual care. In the current analysis, our primary outcome was the proportion of patients with improvement at 12 months follow-up (n=711) in ≥1 LRF stratified by age. RESULTS: At baseline, older patients (n=245, mean age 69.2±3.9 years) had more adverse cardiovascular risk profiles and comorbidities than younger patients (n=579, mean age 53.7±6.6 years). There was no significant variation on the treatment effect according to age (p value treatment by age=0.45, OR 1.67, 95% CI 1.22 to 2.31). However, older patients were more likely to achieve ≥5% weight loss (OR old 5.58, 95% CI 2.77 to 11.26 vs OR young 1.57, 95% CI 0.98 to 2.49, p=0.003) and younger patients were more likely to show non-improved LRFs (OR old 0.38, 95% CI 0.22 to 0.67 vs OR young 0.88, 95% CI 0.61 to 1.26, p=0.01). CONCLUSION: Despite more adverse cardiovascular risk profiles and comorbidities among older patients, nurse-coordinated referral to a community-based lifestyle intervention was at least as successful in improving LRFs in older as in younger patients. Higher age alone should not be a reason to withhold lifestyle interventions in patients with CAD.